An Approach for the Dynamic Reliability Assessment of the Digital Power Control System for Nuclear Reactor - Gui, Maolei; Sui, Yang; Ding, Rui; Xing, Shangpeng; Yu, Tao; Xu, Jintao; Yang, Baosong; Meng, Fanpeng (Frontiers in Energy Research, 2022)
The digital power control system for nuclear reactor (DPCSNR) for nuclear power plant is of dynamic characteristics including dynamic interaction, time dependence, and causal relationship uncertainty, and it is of great significance to assess its dynamic reliability. In this paper, the dynamic fault tree (DFT) analysis (DFTA) method was firstly used to establish the DFT characterizing the dynamic interaction for the DPCSNR. Then, the dynamic Bayesian network (DBN) method was used to transform the DFT to the initial DBN (IDBN) model characterizing the dynamic interaction and time dependence for the DPCSNR. Furthermore, the fuzzy mathematics (FM) method was used to modify the conditional probability table (CPT) characterizing the causal relationship uncertainty in the IDBN model, and to establish the DBN model characterizing the dynamic interaction, time dependence, and causal relationship uncertainty for the DPCSNR. Finally, the DBN model was applied to obtain the reliability curve and to identify the critical events for the DPCSNR, its effectiveness was verified by comparing the result from the DBN calculation with that from Monte Carlo (MC) simulation, and an approach for the dynamic reliability assessment of the DPCSNR was proposed with respect to its dynamic interaction, time dependence, and causal relationship uncertainty.